A new low-cost water loop suitable for BiTe thermogenerators - Juanico, Luis Eduardo (2013)
This paper presents a new design for a thermogenerator suitable for working on low-temperature (up to 175°C) BiTe modules. Its improvement is related to the cooling system that is a low-cost modular device based on domestic hotwater radiators working in a natural-convection loop. Thermal and cost analyses were performed, showing that a competitive 1kW unit could be built (with a specific cost of 21,300 U$D/kW) by optimizing the whole cooling system to work on the new high-temperature (up to 320°C) BiTe modules recently launched, while present commercial thermogenerators cost about 60,000 U$D/kW. This novel design has not been claimed in an invention patent application since it is intended for use in the open market worldwide.